The Digital Learning Capability and Sustainable Skills Development: A Human Resource Approach to Quality Education - Sari Budiarti; Anggun Permata Husda; Tegowati Tegowati; Risya Rosyida (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2026)
The aim of this research is to evaluate how digital learning capabilities impact the development of sustainable skills among students in higher education institutions. This study also investigates the roles played by learning engagement, learning skills, and psychological capital as mediators. Because the increase in access to educational technology has not consistently been followed by a sustainable improvement in skills that meet future needs, this issue is important to discuss. This quantitative research was conducted using survey methods. The data collection method is a Likert scale questionnaire given to students as respondents. The data analysis method is PLS SEM (Partial Least Squares Structural Equation Modeling). The research results show that digital learning ability does not directly become the main determinant of sustainable skill development; instead, it functions thru mediation mechanisms. Engagement learning has proven to be the most dominant mediator. Psychological Capital also has a significant impact. Agility, on the other hand, has a weaker influence. These results indicate that learning engagement and psychological components are crucial in transforming digital capabilities into sustainable skills thru complex and hierarchical serial mediation patterns. Based on the research findings, this article suggests that educational institutions should not only focus on providing technology but also on enhancing student learning engagement and strengthening their psychological capacities so that they can achieve high-quality education.